2022
DOI: 10.1111/opo.12992
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interocular differences on binocular visual performance after inducing forward scattering

Abstract: To assess binocular visual performance by means of binocular summation on visual function after inducing monocular forward scattering, and to study the influence of interocular differences on ocular parameters. Methods:Seven young healthy subjects were recruited. Four Bangerter foils and five fog filters were used to induce monocular forward scattering. To analyse the impact of the scatter, visual acuity, contrast sensitivity, visual discrimination capacity and distance stereoacuity were measured binocularly w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(26 citation statements)
references
References 88 publications
(231 reference statements)
6
20
0
Order By: Relevance
“…This was consistent with results from a study by Castro-Torres et al 27 which showed no difference between participants’ mean baseline photopic HCVA and when Hoya filters (Fog A, B & A + B) and B + W Fog_1 filter were used. This trend was also in line with another study by Martino et al 28 in which they assessed VA binocularly wearing different Fog filters in the dominant eye and reported that on average, VA reduced by only one line.…”
Section: Discussionsupporting
confidence: 90%
“…This was consistent with results from a study by Castro-Torres et al 27 which showed no difference between participants’ mean baseline photopic HCVA and when Hoya filters (Fog A, B & A + B) and B + W Fog_1 filter were used. This trend was also in line with another study by Martino et al 28 in which they assessed VA binocularly wearing different Fog filters in the dominant eye and reported that on average, VA reduced by only one line.…”
Section: Discussionsupporting
confidence: 90%
“…For low‐ and high‐contrast VA, the BS ratio (BS VA ), which characterises the binocular visual performance, 8,17,23 was calculated by dividing the binocular VA value by the best monocular finding following Equation 24 : The conversion from logMAR to decimal VA values was as follows:BSVAgoodbreak=VAbinVAbest_monwhere 0.25emVAbin corresponds to the value of binocular VA and VAbest_mon to the best monocular finding (the highest of the two monocular values).…”
Section: Methodsmentioning
confidence: 99%
“…The latter is defined as the capacity of the visual system to see the surrounding environment in depth. This binocular visual performance is influenced by several other factors including refractive error 19 , pupil size 20 , ocular pathologies 21 , 22 , and interocular differences 23 , 24 . An interocular difference is the difference between the two eyes for a determined ocular parameter.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, an important phenomenon known as intraocular scattering may be responsible for an increase in these interocular differences. When this phenomenon affects one eye more than the other, interocular differences cause a deterioration in binocular visual performance 18 , 24 , 29 . An increase in intraocular scattering results in a veiling luminance on the retina which worsens the retinal image quality 24 , 30 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation